Development of a Smart Hold to Provide Realistic Feedback for Screen Climbing Contents - Sung, Bokyung; Ko, Ilju (International Journal of Engineering and Technology, 2018)
Background/Objectives: Screen Climbing requires additional feedback that can overcome the limitations of the climber being aware of what is going on because the content is using only projected images.Methods/Statistical analysis: Smart hold was designed to provide two realistic types of feedback. One is the visual feedback provided through the three-color light-emitting diode (LED) and the other is the haptic feedback felt by the hands through the vibration actuator. These are both provided by a single control board. Two screen climbing contents were developed to utilize the visual feedback using LED smart holds with haptic feedback via vibration actuators.Findings: The evaluation of usability was conducted for the screen climbing contents that utilized the smart hold. The average and lowest scores in the immersion element were 4.16 and 3.08, respectively, which indicated that high satisfaction scores were obtained for realistic feeling, concentration, and interest viewpoints compared to existing indoor climbing results. The average and lowest scores of the interaction element were 4.18 and 3.63, respectively, which showed high satisfaction levels in terms of immediacy, intuitiveness, and reward viewpoints with regards to the interface of the screen climbing content. Finally, the average and lowest scores of the physical activity element were 4.07 and 3.75, respectively, which showed high satisfaction levels in terms of the movements and safety viewpoints of screen climbing.Improvements/Applications: The evaluation results showed high satisfaction levels since the average score was 4.13. However, this evaluation was limited somewhat because the usability evaluation was conducted with independent single players only.Â Â